(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Wheat, rice and maize contribute approximately two-thirds of the energy in human meals, and the basic foundations of human supplies are four main agricultural systems in which these grains are produced. In these systems, yield per unit time and land has risen significantly over the last 30 years as a consequence of stepped up crop management including better plasma, higher fertilizer inputs, cultivation of two or more crops year on the same piece of land and irrigation. The ongoing development of these four systems will rely mostly on meeting future food needs while limiting cultivated area growth. However, the ways in which additional intensification has been accomplished will vary significantly from the past, since the exploitable gap between average farm yields and genetic yield potential is narrowing. Today, the pace of growth in yield potential is considerably lower than anticipated. Thus, in each of these main cereal systems, average farm yields must approach 70%-80% of the theoretical production limit within 30 years. Consistent production at this high levels without causing environmental harm needs improved soil quality and accurate control of all time and space production variables. The extent of the scientific difficulty linked to these goals is addressed. In order to satisfies the anticipated rise in food demand, significant scientific discoveries must occur in fundamental plant physiology, ecophysiology, and soil science.